Numerical simulations of pore isolation and competition in idealized micro-spall process. (April 2019) - Aniszewski, Wojciech; Zaleski, Stéphane; Llor, Antoine; Malan, Leon
Highlights: A robust computational method involving Free Surface approximation and Volume of Fluid with explicit geometric reconstruction is employed to model bubble dynamics for a large bubble cluster. The choice of boundary conditions corresponds to "ballistic" expansion in which rapid expansion causes bubble isolation, subsequent deceleration leads in turn to a 'competition' phenomenon These two regimes depend solely on Weber number, which is captured by the simulation results. Pressure evolution and appearance of regimes agrees with analytical predictions. Original results could substitute a basis for modelling on a larger scale. Abstract: The 'micro-spall' phenomenon is a variant of fragmentation process—or spall fracture—that is traditionally discussed in context of solid materials (metals). However it concerns situations in which the medium is fully or partially melted —be it due to kinetic impact, detonation or laser loading. The phenomenon takes place at sub-micrometer and sub-microsecond scales making it inaccessible to direct experimental observation; so far, investigations have been restricted to observations of late time "post-mortem" fragments. In this context, it becomes a viable approach to apply analysis using numerical description for fluids. This work presents such an application for an idealized rapid uniaxial (one-dimensional) system expansion. Cavitation in the medium is represented by including vacuous pores or cavities with surface tension whose growth and interaction are traced in time. The simulations reveal two main regimes of pore growth regulated by a characteristic Weber number.